Interferon Genes Are Influenced by 17β-Estradiol in SLE - Singh, Ram P.; Hahn, Bevra H.; Bischoff, David S. (Frontiers in Immunology, 2021)
Recent evidence suggests the existence of a nexus between inflammatory pathways and the female sex hormone 17β-estradiol, resulting in increased interferon-stimulated genes (ISGs), autoantibodies, and dysregulation of immune cells in SLE. However, the molecular mechanisms and the effect of estradiol on candidate target genes and their pathways remains poorly understood. Our previous work suggests that female SLE patients have increased estradiol levels compared to healthy controls. In the present study, we explored the effects of 17-estradiol treatment on expression of IFN (interferons)-stimulated genes and pro-inflammatory cytokines/chemokines. We found significantly increased (5-10-fold) expression of IFN-regulated genes in healthy females. Furthermore, we found significantly increased plasma levels of IL-6, IL-12, IL-17, IL-18, stem cell factor (SCF), and IL-21/IL-23 in SLE patients compared to healthy controls, and those levels positively correlated with the plasma levels of 17-estradiol. In addition, levels of IL-21 positively correlated with the SLE disease activity index (SLEDAI) score of SLE patients. In vitro treatment of PBMCs from either SLE patients or healthy controls with 17-estradiol at physiological concentration (~50 pg/ml) also significantly increased secretion of many pro-inflammatory cytokines and chemokines (IL-6, IL-12, IL-17, IL-8, IFN- MIP1, and MIP1) in both groups. Further our data revealed that 17-estradiol significantly increased the percentage of CD3+CD69+ and CD3+IFN+ T cells; whereas, simultaneous addition of 17-estradiol and an ER inhibitor prevented this effect. Collectively, our findings indicate that 17-estradiol participates in the induction of pro-inflammatory cytokines and chemokines and further influences interferon genes and pathways.